The social significance of barking in New Zealand dogs (Canis familiaris) : a thesis submitted in partial fulfilment of the degree of Doctor of Philosophy in Veterinary Science at Massey University, Palmerston North, New Zealand - Flint, Elsa Louise (Massey University, 2012)
In Auckland, New Zealand, approximately one third of annual complaints to authorities about dogs (Canis familiaris) are due to barking. Despite a recent increase in research in this area, further work is needed to achieve a greater understanding of the behaviour and its impact on society and to establish humane and effective strategies to manage and control unwanted barking. In order to gain more information on problem barking in New Zealand, a survey was sent to two thousand people randomly selected from the electoral roll. The survey evaluated the demographics of dog owners in New Zealand and investigated how potentially disturbing the New Zealand public consider barking to be and why they consider it to be disturbing. The aetiology of problem barking was evaluated in a retrospective study of 107 cases of problem barking presented to an Auckland animal behaviour clinic over a two -year period. The effects of barking on human response were evaluated in a study that exposed 79 volunteer students to recordings of the two main types of barking (barking due to separation anxiety and barking due to territorial guarding). Risk factors for the occurrence of problem barking and for people being bothered by barking were established. Average daily parameters for barking in dogs left at home during the day, that were not problem barkers were established to provide a baseline with which barking complaints could be compared. This was achieved by recording dogs belonging to volunteers over an eight-hour period for five days. Common triggers for barking were established by asking owners to document barking events while they were at home over 24 hours for seven days. Potential methods of preventing and managing problem barking were identified by comparing husbandry protocols used with 107 problem dogs to those used with 80 dogs that were not problem barkers. The typical dog owner in New Zealand was profiled as a person aged between 18 and 55 years, with a positive personality score, educated to secondary school level or above and living in a rural or suburban area and in a house rather than a flat. In addition, the typical dog owner tends to be married or in a de facto relationship with children over the age of one year, considers pet dogs to be very important to society and does not consider a dog bite likely to represent a serious health risk. A typical non-dog owner is likely to be over 65 years, have a university education, live alone in a flat, consider that pet dogs are not very important to society and have a negative personality score. Results confirmed that barking is regarded as a significant problem by many in New Zealand society. Barking and howling were ranked as significantly more annoying than other common suburban noises including lawn mowers, skill saws, and crying babies. Risk factors for being bothered by daytime barking were: age (>35years), being home during the day, not owning a dog, and considering a dog bite to be a serious health risk. Risk factors for being bothered by night-time barking were: being divorced, considering dog bites to pose a serious health risk and having been frightened by a dog. People were also more likely to be disturbed by night-time barking if they had a child under one year of age and if English was not their first language. Two types of barking were particularly bothersome, barking due to separation anxiety, and barking associated with territorial guarding. Students who listened to examples of these two bark types found them equally irritating or difficult to ignore but felt most sorry for dogs barking due to separation anxiety. Risk factors predisposing most to the occurrence of problem barking due to separation anxiety included; leaving dogs alone for more than four hours, keeping only one dog, lack of owner experience with keeping a pet dog, not providing a morning walk and lack of provision of toys and bones. Risk factors for problem territorial barking included; lack of daily training, lack of owner experience with keeping a pet dog, not providing a morning walk and lack of provision of toys .Common triggers for barking that was not due to anxiety were predominantly associated with human activities (63% of triggers were human actions). Normal parameters for barking in 40 suburban dogs were established at an average of 0.54 bouts per hour (range 0-3.5) with an average length per bout of 30 seconds. Information from this study will be useful in implementing strategies for the prevention and management of problem barking. Such strategies might include educating owners and new puppy owners about husbandry techniques that will help prevent problem barking and establishing pre-pet counselling in veterinary clinics. The average barking parameters established may be used to help assess cases of barking reported to the authorities.
Keywords: Dog barking; Barking dogs; Dog owners, New Zealand; Attitudes to dog barking; Dog behaviour; Dog ownership